Determinação de cepas de Wolbachia em populações naturais de Solenopsis spp. (Hymenoptera: Formicidae) analisadas via Multilocus Sequence Typing (MLST): diversidade genética, coevolução e recombinação - Martins, Cíntia [UNESP] (2014)
Insects/microorganisms interactions are broad and occurs in many different ways with symbiont bacteria of insects playing many roles, most unknown, on the biology if its host. What was considered a single eukaryotic organism is actually an aggregate of many different organisms which lead to a change in the way we study organisms, leading to a more holistic approach. Within this vast but relatively unknown world of microorganisms in association with insects are the bacteria of the genus Wolbachia (Class Alphaproteobacteria, Order Rickettsiales) widely distributed in arthropods and maternally transmitted, causing several reproductive alterations in the host, and their occurrence in natural populations being of great interest in the biological control of insects. Its distribution in ants is poorly explored and little is known about the interaction with the Solenopsis genus which includes native species from South America. This genus includes species cosmopolitan distributed and in Brazil they are widely distributed being preferentially associated with areas of human activity. This study aimed to analyze the genetic diversity of samples of nests from native populations of Solenopsis species infected by Wolbachia by sequencing the five genes comprising the Wolbachia multilocus, and also the wsp gene in order to characterize the strains and establish phylogenetic inferences between them. Furthermore test the hypothesis of coevolution between ants and its Wolbachia strains and recombination between found strains. With the sequencing and analysis of five genes comprising the Wolbachia multilocus (gatB, coxA, hcpA, ftsZ e fbpA) totaling 2079 bp the following results are highlighted: i. the record of 15 previously unknown new strains, ii. the record of 11 previously unknown new alleles, iii. phylogenetic relationship between the strains found here presents a polyphyletic pattern, indicative of the complexity of the evolutionary history of strains ...